Does treatment delay for blunt cerebrovascular injury affect stroke rate?: An EAST multicenter study. Issue 11 (November 2022) - Appelbaum, Rachel D; Esposito, Emily; Spaulding, M Chance; Simpson, Joshua P; Dunn, Julie; Zier, Linda B; Burruss, Sigrid; Kim, Paul P; Jacobson, Lewis E; Williams, Jamie M; Nahmias, Jeffry; Grigorian, Areg; et al.
Highlights: BCVIs receive medical therapy early. No increased stroke rates with necessary delays. Studies needed for ideal time of therapy initiation. Abstract: Background: The purpose of this study was to analyze injury characteristics and stroke rates between blunt cerebrovascular injury (BCVI) with delayed vs non-delayed medical therapy. We hypothesized there would be increased stroke formation with delayed medical therapy. Methods: This is a sub-analysis of a 16 center, prospective, observational trial on BCVI. Delayed medial therapy was defined as initiation >24 hours after admission. BCVI which did not receive medical therapy were excluded. Subgroups for injury presence were created using Abbreviated Injury Scale (AIS) score >0 for AIS categories. Results: 636 BCVI were included. Median time to first medical therapy was 62 hours in the delayed group and 11 hours in the non-delayed group ( p  < 0.001). The injury severity score (ISS) was greater in the delayed group (24.0 vs the non-delayed group 22.0, p  <  0.001) as was the median AIS head score (2.0 vs 1.0, p  <  0.001). The overall stroke rate was not different between the delayed vs non-delayed groups respectively (9.7% vs 9.5%, p  = 1.00). Further evaluation of carotid vs vertebral artery injury showed no difference in stroke rate, 13.6% and 13.2%, p  = 1.00 vs 7.3% and 6.5%, p  = 0.84. Additionally, within all AIS categories there was no difference in stroke rate between delayed and non-delayed medical therapy (all N.S.), with AIS head >0 13.8% vs 9.2%, p  = 0.20 and AIS spine >0 11.0% vs 9.3%, p  = 0.63 respectively. Conclusions: Modern BCVI therapy is administered early. BCVI with delayed therapy were more severely injured. However, a higher stroke rate was not seen with delayed therapy, even for BCVI with head or spine injuries. This data suggests with competing injuries or other clinical concerns there is not an increased stroke rate with necessary delays of medical treatment for BCVI.